Differences in Levels of Knowledge and Attitudes about Reproductive Health among Students of the Faculty of Health and Non-Health Faculties in Semarang City - Aprianti Aprianti; Respati Wulandari; Dwi Eko Waluyo (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
Background: Adolescence is a period that is vulnerable to risky sexual behavior. This study aimed to describe the reproductive health knowledge and attitudes of students at the faculty of health and non-health faculties.Methods: It is research with quantitative methods using a cross-sectional design. The variables of this study are the level of knowledge and attitudes about reproductive health—data collection techniques with online surveys. Data analysis used descriptive statistics and bivariate analysis (Mann-Whitney test).Results: Respondents with a good level of knowledge and attitudes about sexual reproductive health at the health faculties were higher than respondents at the non-health faculties (78 Vs. 61 people and 68 Vs. 42 people). The knowledge and attitudes of respondents in the health and non-health faculties were significantly different (?=19; p = 0.009 and ?=27.95; p = 0.001).Conclusion: Health promotion is needed for students, especially non-health students, to increase knowledge and attitudes about reproductive health to prevent risky sexual behavior among students